Acceso a información y atención en salud bucal en niños peruanos, 2019 - Espinoza Gonzaga, Gianella Nathaly (2022)
The purpose of this descriptive study was to determine access to information and children under 12 oral health care based on the Demographic and Family Health Survey published in 2019 (ENDES -2019).The sample was comprised of 26 196 children under 12. After analyzing the results, they show that 61,2 % of children had access to oral health information in Peru and 60.7% of children have receive a dental service or had an odontologist appointment. Finally, it is concluded that many children under 12 have had access to oral care information and a dental service according to the Demographic and Family Health Survey published in 2019.